Framing of Tempo's News Coverage on the Failure to Realise the Nawacita Programme in the Headline "Nawadosa Jokowi" - Soediro, Rayhan Althaaf; Samodro, Dewanto (LEGAL BRIEF, 2025)
This study aims to examine the framing employed by Tempo in its coverage of the 10th anniversary of Jokowi's administration, focusing on issues in the priority sectors of Nawacita. This study employs a descriptive qualitative research method with data collection techniques of observation and documentation, and data analysis using Robert Entman's framing model. Robert Entman and Erwing Goffman's framing theory is used in this study to strengthen the analysis results and understand the background of Tempo as a media outlet that can influence its framing in news coverage. The results of this study indicate Tempo's critical stance toward the implementation of the Nawacita program over the past 10 years, with Tempo aligning itself with the opposition. This alignment is demonstrated through news articles with negative news values while still adhering to journalistic ethics